2020
DOI: 10.31933/dijdbm.v1i2.157
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Return on Investment, Current Ratio, Debt to Equity Ratio , Earning Per Share,and Firm Size to the Dividend Pay Out Ratio in Banking Industries Listed at Indonesia Stock Exchange Period 2013-2018

Abstract: This study aimed to examine the factors that influence the ratio of dividend payments in the banking industry. These factors include return on investment, current ratio, debt to equity ratio, earnings per share, and firm size. The technique for sampling using purposive sampling while the sample used in this study was 6 banking companies listed on the Indonesia Stock Exchange in 2014-2018. The analytical method used in this study was a panel data regression model (a combination of time series and cross section)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
1
16

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 4 publications
0
4
1
16
Order By: Relevance
“…The study findings also contradict findings by Nyere and Wesson (2019) in South Africa who found a positive significant effect for industrial companies and Ogundajo et al (2019) in Nigeria who found a negative significant effect for manufacturing firms. In Asia, the findings contradict the findings by Brahmaiah et al (2018) in India and Rahmadi (2020) for banks listed at the Indonesia Stock Exchange.…”
Section: Stratford Peer Reviewed Journals and Book Publishing Journal...contrasting
confidence: 90%
See 2 more Smart Citations
“…The study findings also contradict findings by Nyere and Wesson (2019) in South Africa who found a positive significant effect for industrial companies and Ogundajo et al (2019) in Nigeria who found a negative significant effect for manufacturing firms. In Asia, the findings contradict the findings by Brahmaiah et al (2018) in India and Rahmadi (2020) for banks listed at the Indonesia Stock Exchange.…”
Section: Stratford Peer Reviewed Journals and Book Publishing Journal...contrasting
confidence: 90%
“…Prior findings have recorded significant correlation between various firm characteristics and dividend payout. For instance, Kiangi et al (2022), Nyere and Wesson (2019), Ogundajo, Enyi, Akintoye, and Dada (2019), Brahmaiah, Srinivasan, and Sangeetha (2018) and Rahmadi (2020) found a significant correlation between dividend payout and firm size whereas Pattiruhu and Paais (2020), Katakwar, Tenguriya, Chhajer, and Mehta (2021) and Okoro, Ezeabasili, and Alajekwu (2018) Considering foregoing studies together with several others published in other emerging and developing countries, this study wanted to establish by providing empirical evidence of effects of bank characteristics on dividend payout for large commercial banks. The study was directed by the ensuing null hypotheses: H01: Bank size has no significant effect on dividend payout of Tier I banks in Kenya.…”
Section: Empirical Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Kebijakan pembayaran dividen harus didukung dengan ketersediaan aset lancar (kas) yang cukup guna pembayaran dividen tersebut. Pada penelitian Nehe et al, (2021), likuiditas memiliki pengaruh negatif dan pada beberapa penelitian lainnya justru memberikan pengaruh (Arsyad et al, 2021;Fadillah & Eforis, 2020;Herawati & Fauzia, 2018;Jackson & Laksmiwati, 2021;Kengatharan, 2021;Lie & Osesoga, 2020;Martha & Juliani, 2018;Rahmadi, 2020;Tahir & Mushtaq, 2016) Aspek lain pendorong kebijakan pembayaran dividen yakni rasio leverage. Tidak mudah bagi entitas dengan leverage yang tinggi untuk memutuskan apakah akan mendistribusikan dividen atau tidak kepada pemilik.…”
Section: Pendahuluanunclassified
“…Adanya pengaruh yang tidak signifikan, dikarenakan sebagian sampel penelitian ini merupakan perusahaan dengan kategori besar namun membagikan dividen tidak lebih tinggi daripada perusahaan dengan size yang relatif kecil. Penelitian ini diperkuat hasil penelitian (Simbolon & Sampurno, 2017), (Suliana & Susanti, 2017) (Simbolon & Sampurno, 2017), (Indrawan, 2017), (Sari & RM, 2017), (Cahyani & Badjra, 2017), (Zaman, 2018), (Anwar, 2018), (Fitriati et al, 2018), (Anshar & Warimin, 2020), dan (Tania Rahmadi, 2020). Variabel DER mampu memediasi pengaruh ROA terhadap DPR, akan tetapi variabel DER tidak mampu memediasi pengaruh asset growth dan firm size terhadap DPR.…”
Section: Pengaruh Firm Size Terhadap Dprunclassified